2003
DOI: 10.1002/j.2161-007x.2003.tb00266.x
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of the Role of Religion for Family Members of Lesbian, Gay Male, or Bisexual Male and Female Individuals

Abstract: Religious faith i s an important aspect of many people's lives, but the doctrinal teachings of many faiths are that homosexuality is a sin. Little is known about the impact of these teachings on the family members of lesbian, gay male, or bisexual male and female (LGB) individuals. Eightyeight family members of LGB individuals were surveyed regarding the role of religion in acceptance of their family member and how they reconciled any conflicts between religious beliefs and family member's sexual orientation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Given the outright acceptance experienced by several participants, it is clear that, despite denominational injunctions, some members were compelled to be accepting of the men because of their faith convictions. For some religious people faith mandates unconditional love for all (Lease and Shulman 2003) and this likely motivated our participants to maintain their ties to churches. This argument is consistent with findings on White (Sweasey 1997, Yip 1998, Lease and Shulman 2003 and Black (Crawford et al 2002) non-heterosexuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the outright acceptance experienced by several participants, it is clear that, despite denominational injunctions, some members were compelled to be accepting of the men because of their faith convictions. For some religious people faith mandates unconditional love for all (Lease and Shulman 2003) and this likely motivated our participants to maintain their ties to churches. This argument is consistent with findings on White (Sweasey 1997, Yip 1998, Lease and Shulman 2003 and Black (Crawford et al 2002) non-heterosexuals.…”
Section: Discussionmentioning
confidence: 99%
“…This erroneous assumption has reified gay/lesbian dominance and bisexual absence in religious studies of non-heterosexuals (for examples, see Oswald 2001, Lease and Shulman 2003, Lease et al 2005, Ward 2005). Even so, because few studies have examined the religious experiences of non-heterosexual Blacks, we know little of bisexual Black men's experiences with religion and spirituality.…”
Section: Why Focus On Bisexual Black Men?mentioning
confidence: 99%
“…In the clinical literature, which contains articles, books, and chapters from both clinical psychology as well as pastoral counseling and social work, there is open debate on many topics including the morality of homosexuality, addressing the specific clinical needs of gay and lesbian clients, the efficacy of reparative therapy, and the role of pastoral counseling within not only the gay and lesbian community as a whole, but within the religious gay and lesbian community as well. As this article attempted to review the theoretical and research literature on the interactions between gay and religious identities, I leave a more detailed review of the clinical writings in this area for future work (for more information in this area, see Buchanan, 2001;Dallas, 1996;Davison, 1991;Donaldson, 1998;Haldeman, 1991;Hodge, 2005;Lease & Shulman, 2003;Throckmorton, 1998;Yarhouse, 1998).…”
Section: Clinical Literaturementioning
confidence: 99%
“…In addition, Herek, Gillis, and Cogan (2009) reported that religious sexual minorities (Le., reported a religious identity, believed in a higher power, or attended religious services) were more likely to internalize heterosexism. Therefore, some gay and lesbian individuals have a dichotomous view of religion and sexual orientation (Lease & Shulman, 2003;Ritter & O'Neill, 1989). …”
Section: Statement Of Problemmentioning
confidence: 99%